Connotation and Myth: Language Expression of Gen Z through WhatsApp Emoticon - Sri Wulandari; Aisya Fauzia Rahma; Puri Bakthawar (Program Studi Sastra Indonesia, Fakultas Ilmu Budaya, Universitas Diponegoro, 2024)
Compared to previous generations, Generation Z (Gen Z) lives in a different lifestyle and culture. Since their youth, Gen Z cannot be separated from digital and technological aspects in their daily life. In communication, it can be assumed that Gen Z is familiar with the use of WhatsApp as their primary communication medium. It is proven that in the period of the Covid-19 pandemic, WhatsApp was crucial as a communication medium by Gen Z. On the other hand, communication patterns in digital space are quite different from traditional verbal communication. There are many features in WhatsApp, one of them is emoticon features, that make the process of language interpretation become ambiguous and multi-interpretative. This study aims to uncover that language phenomenon, especially by analysing connotations and myths represented in WhatsApp emoticons used by Gen Z, using the perspective of Roland Barthes’ semiotic theory. The results of this research show that through the WhatsApp emoticons used by Gen Z, it can be concluded that WhatsApp emoticons are often used arbitrarily by Gen Z, which then implies certain connotative meanings, which are also related to the context of the conversation being built. The myth that underlies this phenomenon is the cultural background of Gen Z as a generation that cannot be separated from technological aspects, thus allowing for their authentic uniqueness in language styles, caused by the mediated language through digital platforms such as WhatsApp.